Segmentation of Passenger Preferences for Spending Rate and Product Positioning at Terminal 3 Soekarno Hatta International Airport - Bahmi, Yulizen; Handrikovaro, Mario; Oktavia Rini, Ade; Simarmata, Juliater (DINASTI RESEARCH, 2025)
The purpose of this study is to understand the segmentation, shopping tendencies, and commercial product preferences of passengers at Terminal 3 Soekarno Hatta Airport. The research design uses a quantitative method as an approach. Data collection was conducted through questionnaires randomly distributed to 385 respondents as a sample, using the Lemeshow formula with a 95% confidence level, a 5% margin of error, and a 50% maximum estimation. The results of the study show that passenger segmentation at Terminal 3 Soekarno Hatta Airport is dominated by solo travelers, families, and business groups. The majority of passengers (62%) tend to shop within the price range of IDR 50,000 – 250,000, with the main product preference being food and beverages such as coffee shops, bakeries, and cafes available in the waiting areas and departure zones.